Unidade plural: tensões entre o constitucionalismo plurinacional e os discursos indígenas na construção do novo Estado boliviano - Valle, Aline de Souza Vasconcellos do (2021)
In the first decade of the 21st century, Bolivia emerged as a place of political and social effervescence on the international stage. This was due to the strength of the indigenous movements, the rise of a coca growers president with strong ethnic discourse, the emergence of new constitutional principles and legal norms, based on elements of indigenous culture and the promise of refoundation of the State, through the shaping of a plurinational State, as provided for in the Bolivian Charter of 2009. In this context, the thesis analyses the historical process of building indigenous autonomy in Bolivia, focusing on the relations between the new constitutional principles and norms used for the implementation of the plurinational state model, analysing the history of autonomic indigenous movements and their relationship with the history of indigenous rights in Bolivia, reflecting on the tensions between state discourse and autonomic indigenous movements in the post-constitutional period (2009-2017), as well as the tensions between the different indigenous demands present in the country, using as main sources the Bolivian Constitution, the Electoral Law, Jurisdictional Ruling Law, Law of Autonomy, Mother Earth Framework Law and Integral Development for Living Well, in addition to documents from state agencies such as the Vice Ministry of Decolonization, the Vice Ministry of Autonomies, magazines and communiqués from indigenous organizations such as the CIDOB, CONAMAQ, APG and autonomous statutes of Charagua, Jesús de Machaca and Tarabuco.